COMMUNICATION STYLE OF SRIWIJAYA 94.3 FM RADIO ANNOUNCERS: A CASE STUDY OF RELATIONSHIPS WITH LISTENERS - Putri; Azarkasyi, Badarudin (International Journal of Multidisciplinary Reseach, 2025)
This study examines the communication style of Sriwijaya 94.3 FM radio announcers and their role in building closeness with listeners amid the increasingly digital audio media landscape. Using a qualitative approach, data were collected through program observations, in-depth interviews with announcers and listeners, and analysis of social media documentation. The findings indicate that announcers employ a warm and empathetic communication style, rooted in local culture, and highly responsive to listener interactions and feedback. Consistent relationship-building through on-air rituals, public appreciation, and topic continuity strengthens parasocial bonds between announcers and listeners. This approach not only creates positive emotional experiences but also fosters audience loyalty toward the radio station. The study highlights the importance of humanistic and adaptive communication strategies for local radio in maintaining relevance and closeness with listeners in the digital era, while providing insights for developing more effective broadcasting practices.